2004
DOI: 10.1016/j.joca.2003.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for osteoarthritis: genetics11Supported by Procter & Gamble Pharmaceuticals, Mason, OH

Abstract: Although the multifactorial nature of osteoarthritis (OA) is well recognized, genetic factors have been found to be strong determinants of the disease. Evidence of a genetic influence of OA comes from a number of sources, including epidemiological studies of family history and family clustering, twin studies, and exploration of rare genetic disorders. Classic twin studies have shown that the influence of genetic factors is between 39% and 65% in radiographic OA of the hand and knee in women, about 60% in OA of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
92
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(104 citation statements)
references
References 55 publications
1
92
0
1
Order By: Relevance
“…Both familial and twin studies find support for genetic influences on the formation of osteoarthritis (e.g. Jonsson et al, 2003;Manek et al, 2003;Spector & MacGregor, 2004;Zhai et al, 2004;Min et al, 2005). Results from various twin and familial studies show that overall heritability of osteoarthritis averages around 0.50; in other words, 50% of phenotypic variability in osteoarthritis can be accounted for by differences in genotype (e.g.…”
Section: Genetic Influencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both familial and twin studies find support for genetic influences on the formation of osteoarthritis (e.g. Jonsson et al, 2003;Manek et al, 2003;Spector & MacGregor, 2004;Zhai et al, 2004;Min et al, 2005). Results from various twin and familial studies show that overall heritability of osteoarthritis averages around 0.50; in other words, 50% of phenotypic variability in osteoarthritis can be accounted for by differences in genotype (e.g.…”
Section: Genetic Influencesmentioning
confidence: 99%
“…Results from various twin and familial studies show that overall heritability of osteoarthritis averages around 0.50; in other words, 50% of phenotypic variability in osteoarthritis can be accounted for by differences in genotype (e.g. Ingvarsson et al, 2000;Lanyon et al, 2000;Jonsson et al, 2003;Manek et al, 2003;Spector & MacGregor, 2004). However, it is important to note that there is research suggesting that twin studies may overestimate heritabilities (Zhai et al, 2004).…”
Section: Genetic Influencesmentioning
confidence: 99%
“…Osteoarthritis (OA) is a prevalent joint disease and is a leading cause of disability. Although the exact etiology and pathogenesis of OA are not fully understood, epidemiological and genetic studies indicate that genetic factors are strong determinants in the onset of OA 12. A genetic contribution to OA has been suggested in several epidemiological studies 3.…”
mentioning
confidence: 99%
“…165720) is the most prevalent form of arthritis and a common cause of disability. Epidemiological studies have demonstrated a major genetic component to primary OA, with estimated heritability of 40% for the knee, 60% for the hip, and 65% for the hand (1). Several genome-wide linkage scans have been performed on cohorts of affected sibling pairs or affected relative pairs concordant for hip, knee, or hand OA (reviewed in refs.…”
mentioning
confidence: 99%